2007
DOI: 10.1080/09637480701395580
|View full text |Cite
|
Sign up to set email alerts
|

Content andin-vitroaccessibility of pro-vitamin A carotenoids from Sri Lankan cooked non-leafy vegetables and their estimated contribution to vitamin A requirement

Abstract: Vitamin A deficiency is a public health problem in Sri Lanka, which affects especially pre-school children. Carrots (Daucus carota), pumpkins (Cucurbita maxima), squashes (Cucurbita moschata) and sweet potatoes (Ipomoea batatas) of orange, yellow-fleshed varieties are good sources of provitamin A carotenoids, but have not been studied in Sri Lanka in terms of the food as eaten. The content of carotenoids in each preparation method and the in-vitro accessibility of beta-carotene and alpha-carotene were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…These percentages are consistent with results from previous in vitro digestions with glasshouse grown melons where the digestive stability and the percent micellerization (β-carotene bioaccessibility) did not differ between orange-fleshed honey dew and cantaloupe melons (results not shown). The values for digestive stability are consistent with previously published results in maize ( Zea mays ), cassava ( Manihot esculenta ), drumstick ( Moringa oleiflora ) leaves, carrots ( Daucus carota ), green leafy vegetables, mangoes ( Mangifera indica ), sweet potatoes ( Ipomoea batatas ), squash ( Cucurbita moschata ), and pumpkins ( Cucurbita maxima ) (11, 23-28). There are many factors that affect the intestinal absorption of carotenoids such as the type and quantity of dietary fat, competition among co-consumed carotenoids, the plant or food matrix (29), and cooking.…”
Section: Resultssupporting
confidence: 91%
“…These percentages are consistent with results from previous in vitro digestions with glasshouse grown melons where the digestive stability and the percent micellerization (β-carotene bioaccessibility) did not differ between orange-fleshed honey dew and cantaloupe melons (results not shown). The values for digestive stability are consistent with previously published results in maize ( Zea mays ), cassava ( Manihot esculenta ), drumstick ( Moringa oleiflora ) leaves, carrots ( Daucus carota ), green leafy vegetables, mangoes ( Mangifera indica ), sweet potatoes ( Ipomoea batatas ), squash ( Cucurbita moschata ), and pumpkins ( Cucurbita maxima ) (11, 23-28). There are many factors that affect the intestinal absorption of carotenoids such as the type and quantity of dietary fat, competition among co-consumed carotenoids, the plant or food matrix (29), and cooking.…”
Section: Resultssupporting
confidence: 91%
“…37 Another study by Hedrén et al 38 showed accessible β-carotene was 39% from sweet potato, 64% from pumpkin, and 47% from cassava, which were all cooked with sunflower oil. Three other studies with this method showed a bioaccessibility of β-carotene of 19% from boiled pumpkin, 39 74% from boiled carrot, 39 and when cooked with vegetable oil, 11–22% from various processed sweet potato, 40 21% from sweet potato, and 39% from pumpkin. 41 Our results of 28% and 53% are also comparable with the results from this in vitro method.…”
Section: Discussionmentioning
confidence: 91%
“…flesh colour, peel type/colour, stage of maturity, pH) and any other informative data, if available, such as origin, soil and climate, size, cultivar, harvest date, preservation and packing medium, will improve the applicability and comparability of data. Cultivar/varietal difference could be quantitative, as in the case of Brazilian mangoes [10], red-fleshed Brazilian papayas [12], citrus cultivars from Florida [13], red tomatoes [14], pandanus fruit [15] and yellow-fleshed sweet potatoes and pumpkin [16]. An example is shown in Table 14.1 for varieties of sweet potatoes and pumpkins found in Sri Lanka.…”
Section: Cultivar or Varietal Differencesmentioning
confidence: 99%
“…An example is shown in Table 14.1 for varieties of sweet potatoes and pumpkins found in Sri Lanka. However, pronounced qualitative and quantitative variations can also be observed as in squashes and pumpkins [16,18,19] (Table 14.1), orange and red-fleshed papaya [12,20] and emberella [21].…”
Section: Cultivar or Varietal Differencesmentioning
confidence: 99%